2014
DOI: 10.1155/2014/758323
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium Involvement in Neurotoxicity

Abstract: The aetiology of neurodegenerative diseases (ND) seems to involve susceptibility genes and environmental factors. Toxic metals are considered major environmental pollutants. Following our study of a case of multiple sclerosis (MS) improvement due to removal of aluminium (Al) and other toxic metals, we have examined the possible relationship between Al intoxication and ND. We used the slow intravenous treatment with the chelating agent EDTA (calcium disodium ethylene diamine tetraacetic acid) (chelation test) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 32 publications
1
35
0
Order By: Relevance
“…EDTA is slowly administered intravenously (infusion lasts about 2 hours) and the time of urine collection following chelation lasts 12 h. Toxic-metal urine contents are expressed in micrograms ( μ g) per g creatinine [47]. Details regarding “chelation test” have already been reported [48]. …”
Section: Chelating Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…EDTA is slowly administered intravenously (infusion lasts about 2 hours) and the time of urine collection following chelation lasts 12 h. Toxic-metal urine contents are expressed in micrograms ( μ g) per g creatinine [47]. Details regarding “chelation test” have already been reported [48]. …”
Section: Chelating Agentsmentioning
confidence: 99%
“…GSH plays a key role in cell resistance against oxidative damage by providing enzymes involved in ROS metabolism with reducing equivalents, by eliminating potentially toxic oxidation products, and by reducing oxidized protein thiols [57]. Recently, we showed that CaNa 2 EDTA treatment of patients affected by Al burden significantly reduced Al intoxication [48]. Moreover, the efficacy of long-term chelation therapy has been shown in the removal of chronic Al intoxication [58].…”
Section: Chelating Agentsmentioning
confidence: 99%
“…These products impair the balance between the prooxidant and antioxidant systems in the body: The shift towards the former is known as "oxidative stress". Oxidative stressmediated toxicity caused by heavy metals mainly involves the liver and kidneys, the central nervous system, and the endocrine system [1][2][3][4]. Which strategies can be adopted against the dangerous effects of toxic metals?…”
Section: Editorialmentioning
confidence: 99%
“…The most commonly used strategy against heavy-metal poisoning is chelation therapy, which promotes metal excretion. This treatment is suggested following both acute and chronic intoxication, and can also be used to remove intoxication caused by a non-heavy metal, such as aluminum [4]. However, new strategies have recently been reported, describing the protective effects of dietary supplements against cadmium and lead toxicity [5].…”
Section: Editorialmentioning
confidence: 99%
“…Environmental exposure to aluminum, as well as to other toxic metals is considered to contribute to cognitive impairment in children living in rural areas [32]. Regarding neurodegenerative diseases, the removal of aluminum improved symptoms of multiple sclerosis [33]. In animal models aluminum has been shown to accumulate in the male and female reproductive systems and was shown to be an endocrine disruptor [34][35][36].…”
Section: Mechanisms For the Suspected Effect Of Human Papilloma Virusmentioning
confidence: 99%